Identification of Binge Eating Disorder Criteria: Results of a National Survey of Healthcare Providers. Issue 4 (1st March 2019) - Chao, Ariana M.; Rajagopalan, Adithi V.; Tronieri, Jena Shaw; Walsh, Olivia; Wadden, Thomas A.
Abstract: Purpose: To determine whether general healthcare providers and adult psychiatrists recognized binge eating disorder (BED) symptoms and features. The aims were to examine how they delineated the core criteria of BED—eating a large amount of food and sense of loss of control over eating—and how their evaluations compared to ratings by BED experts. Design: This is a cross‐sectional study of a nationwide U.S. sample of healthcare providers and a convenience sample of BED experts. Methods: Providers were mailed surveys that asked respondents about their perceptions of a large amount of food and whether they thought case vignettes met thresholds for loss of control. Participants were also asked to select BED diagnostic criteria from a symptom list. Results were analyzed using one‐way analyses of variance with post‐hoc comparisons and chi‐squared tests. Findings: The survey was completed by 405 healthcare providers (response rate of 28.4%). Ratings of a large amount of food did not differ between BED experts and general healthcare providers ( p = .10) or psychiatrists ( p  = .90). Provider groups did not differ significantly on whether five of the six vignettes met thresholds for loss of control ( p > .05). Of the respondents, 93.0% of general healthcare providers and 88.6% of psychiatrists could not correctly identify the diagnostic criteria for BED. Conclusions: Across provider groups, demarcation of a large amount of food and loss of control over eating were relatively consistent. However, general healthcare providers and psychiatrists were not able to correctly identify BED symptoms. Clinical Relevance: Training and education are greatly needed to improve knowledge of the diagnostic criteria for BED.